Longitudinal cellular and humoral immune responses after triple BNT162b2 and fourth full-dose mRNA-1273 vaccination in haemodialysis patients - Becker, Matthias; Cossmann, Anne; Lürken, Karsten; Junker, Daniel; Gruber, Jens; Juengling, Jennifer; Ramos, Gema Morillas; Beigel, Andrea; Wrenger, Eike; Lonnemann, Gerhard; Stankov, Metodi V.; Dopfer-Jablonka, Alexandra; et al. (Frontiers in Immunology, 2022)
Haemodialysis patients respond poorly to vaccination and continue to be at risk for severe COVID-19. Therefore, dialysis patients were among the first for which a fourth COVID-19 vaccination was recommended. However, targeted information on how to best maintain immune protection after SARS-CoV-2 vaccinations in at-risk groups for severe COVID-19 remains limited. We provide, to the best of our knowledge, for the first time longitudinal vaccination response data in dialysis patients and controls after a triple BNT162b2 vaccination and in the latter after a subsequent fourth full-dose of mRNA-1273. We analysed systemic and mucosal humoral IgG responses against the receptor-binding domain (RBD) and ACE2-binding inhibition towards variants of concern including Omicron and Delta with multiplex-based immunoassays. In addition, we assessed Spike S1-specific T-cell responses by interferon  release assay. After triple BNT162b2 vaccination, anti-RBD B.1 IgG and ACE2 binding inhibition reached peak levels in dialysis patients, but remained inferior compared to controls. Whilst we detected B.1-specific ACE2 binding inhibition in 84% of dialysis patients after three BNT162b2 doses, binding inhibition towards the Omicron variant was only detectable in 38% of samples and declining to 16% before the fourth vaccination. By using mRNA-1273 as fourth dose, humoral immunity against all SARS-CoV-2 variants tested was strongly augmented with 80% of dialysis patients having Omicron-specific ACE2 binding inhibition. Modest declines in T-cell responses in dialysis patients and controls after the second vaccination were restored by the third BNT162b2 dose and significantly increased by the fourth vaccination. Our data support current advice for a four-dose COVID-19 immunisation scheme for at-risk individuals such as haemodialysis patients. We conclude that administration of a fourth full-dose of mRNA-1273 as part of a mixed mRNA vaccination scheme to boost immunity and to prevent severe COVID-19 could also be beneficial in other immune impaired individuals. Additionally, strategic application of such mixed vaccine regimens may be an immediate response against SARS-CoV-2 variants with increased immune evasion potential.